P078 Barriers and facilitators to expedited partner therapy: a survey of family physicians in british columbia, canada. (14th July 2019) - Wong, Jason; Consolacion, Theodora; Choi, Alexandra; Zakher, Bernadette; Leong, Jeffrey; Ng, Brian; Pawa, Jasmine; Campbell, Audrey
Abstract : Background: In British Columbia (BC), rates of chlamydia and gonorrhea have been increasing over the last two decades. Expedited partner therapy (EPT)—providing medications to sex partners of patients diagnosed with chlamydia or gonorrhea without a prerequisite medical examination—improves partner treatment, reduces reinfection, and prevents onward transmission. We sought to understand the perspectives of family physicians (FPs) on offering EPT to inform strategies to support this practice. Methods: FPs were invited to complete an online 17-question survey through the mailing list of Divisions of Family Practice (DoFP), geography-based networks of FPs across BC that represent over 90% of FPs. The survey queried practice demographics, experience diagnosing sexually transmitted infections (STIs) in the past year, and perceived barriers and facilitators to EPT to descriptively explore associations between these factors. Results: 146 FPs answered the majority of questions and were included. Most were female (99/146, 67.8%), between 30 and 59 years old (118/146, 80.8%), served an urban or suburban population (107/146, 73.3%), and engaged in general practice (108/146, 74.0%). The median years in practice was 9 (interquartile range: 4–21). The vast majority had diagnosed an STI within the past year (136/146, 93.2%). Most (91.1%) reported diagnosing chlamydia and 45.6% reported diagnosing gonorrhea in the past year. The most commonly reported barriers were having inaccurate information about sex partners (88/146, 60.3%) and medicolegal concerns (87/146, 59.6%). Commonly reported facilitators were having a healthcare professional for follow-up after prescribing EPT (110/146, 75.3%), improved remuneration (93/146, 63.7%), having a legal framework (92/146, 63.0%) and clear clinical guidelines around EPT (87/146, 59.6%). Conclusion: Over 90% of FPs surveyed had diagnosed an STI in the prior year, underscoring the importance of engaging FPs in STI prevention strategies. Developing tools, such as a clear legal framework for EPT and clinical guidelines, may enable FPs to prescribe EPT. Disclosure: No significant relationships.